2022
DOI: 10.1161/circresaha.121.319100
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical HIPPO/MST Signaling via BUB3 and FOXO Drives Pulmonary Vascular Cell Growth and Survival

Abstract: Rationale: The MSTs (mammalian Ste20-like kinases) 1/2 are members of the HIPPO pathway that act as growth suppressors in adult proliferative diseases. Pulmonary arterial hypertension (PAH) manifests by increased proliferation and survival of pulmonary vascular cells in small PAs, pulmonary vascular remodeling, and the rise of pulmonary artery pressure. The role of MST1/2 in PAH is currently unknown. Objective: To investigate the roles and mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 74 publications
(128 reference statements)
0
21
0
Order By: Relevance
“…306,307 Interestingly, recent research revealed that MST1/2, a Hippo component that usually plays an antiproliferative role, supports the abnormal proliferation of PASMCs in pulmonary arterial hypertension via forehead homeobox type O and BUB3. 308 Second, the Hippo pathway could regulate the inflammatory response in the lung. In a bacterial pneumonia model, the relative levels of p-YAP and p-TAZ were decreased in alveolar epithelial type II cells (AECIIs).…”
Section: Dysregulation Of the Hippo Pathway And Human Diseasesmentioning
confidence: 99%
“…306,307 Interestingly, recent research revealed that MST1/2, a Hippo component that usually plays an antiproliferative role, supports the abnormal proliferation of PASMCs in pulmonary arterial hypertension via forehead homeobox type O and BUB3. 308 Second, the Hippo pathway could regulate the inflammatory response in the lung. In a bacterial pneumonia model, the relative levels of p-YAP and p-TAZ were decreased in alveolar epithelial type II cells (AECIIs).…”
Section: Dysregulation Of the Hippo Pathway And Human Diseasesmentioning
confidence: 99%
“…Cell proliferation was assessed using Ki-67 immunostaining as described previously ( 10 , 32 , 34 ). Briefly, cells were washed with PBS, fixed in 4% paraformaldehyde/PBS, and permeabilized using Triton X-100/PBS solution.…”
Section: Methodsmentioning
confidence: 99%
“…Cell growth analysis was performed as described previously ( 10 , 32 , 34 ). Briefly, 300,000 cells per well were plated in a six well plate in cell culture media supplemented with 5% FBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FoxO3a promotes VSMC growth arrest and apoptosis after vascular injury [57,58], suggesting that Aktdependent regulation of FoxOs activity also plays an important role in VSMC biology. Moreover, in VSMCs of human pulmonary arteries, degradation of FOXO3 is promoted by interleukin-6-induced mammalian Ste20like kinases 1/2 expression, which enhances proliferation and inhibits apoptosis in VSMCs to contribute to the pathogenesis of pulmonary arterial hypertension [59].…”
Section: Foxos In Vsmcsmentioning
confidence: 99%